A Highly Sensitive SPR Sensors Based on Two Parallel PCFs for Low Refractive Index Detection - Famei Wang; Chao Liu; Zhijie Sun; Tao Sun; Banghua Liu; Paul K. Chu (IEEE Photonics Journal)
Based on two parallel photonic crystal fibers (PCFs) with D-shape structure, a novel surface plasmon resonance (SPR) sensor with low refractive index (RI) detection at near-infrared wavelengths is described. According to the coupled-mode theory, directional power transfer between the two fiber cores is enhanced by resonant coupling between the surface plasmon modes and fiber core-guided modes. In comparison with corresponding single D-shape PCF, a maximum spectral sensitivity up to 13 500 nm/RIU and resolution of 7.41 × 10−6 RIU for RI detection range between 1.27 and 1.32 are achieved. The proposed two parallel D-shape PCFs-SPR sensor with lower RI detection range offer large potential in the fields of pharmaceutical inspection and pharmaceutical leakage monitoring.